Impacts of a shift in the production and consumption of marine protected resources a case of Suyac island - Go, Pamela; Dela Cruz, Jet; Agustin, Nick (2019)
This is a case study of Suyac Island, a marine protected community in Negros Occidental. It presents the social, economic, and environmental impacts of a shift in the production and consumption of resources from a highly dependent fishing economy that follows the "take-make-use-dispose" regime to a more circular management of resources that is ecotoursim. The study used mixed method to measure and describe the impacts as well as identify endogenous resource management practices. Results revealed that ecotourism on the island improved living conditions through provision of alternative means of livelihood and entrepreneurial opportunities for both men and women. There is also a perceived higher participation, involvement, and volunteerism in the community, Likewise, there are notable actions toward environmental conservation and protection of marine resources. Analysis of the impacts provide support to a circular management of resources, particularly in this case, the marine protected resources. The study underlines the applicability of circular management of marine protected resources and the endogenous practices that necessitated the transition.
Keywords: Marine Protected Areas; Marine resources; Marine Resources Protection; Ecotourism; Resource consumption; Production